The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1086/506003
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Cooling of Bird Eggs Reduces Embryonic Growth Efficiency

Abstract: For many bird embryos, periodic cooling occurs when the incubating adult leaves the nest to forage, but the effects of periodic cooling on embryo growth, yolk use, and metabolism are poorly known. To address this question, we conducted incubation experiments on eggs of zebra finches (Taeniopygia guttata) that were frequently cooled and then rewarmed or were allowed to develop at a constant temperature. After 12 d of incubation, embryo mass and yolk reserves were less in eggs that experienced periodic cooling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
157
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(170 citation statements)
references
References 54 publications
7
157
2
Order By: Relevance
“…Cooler embryonic temperatures can cause longer embryonic periods and decreased developmental efficiency from increased metabolic costs, and thereby compromise postnatal offspring quality [8,18]. The assumption that the absolute length of the embryonic period is an estimate of intrinsic embryonic development rate may be misplaced when embryonic temperature varies extensively, as commonly seen among passerines [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooler embryonic temperatures can cause longer embryonic periods and decreased developmental efficiency from increased metabolic costs, and thereby compromise postnatal offspring quality [8,18]. The assumption that the absolute length of the embryonic period is an estimate of intrinsic embryonic development rate may be misplaced when embryonic temperature varies extensively, as commonly seen among passerines [9].…”
Section: Discussionmentioning
confidence: 99%
“…This assumption may be problematic for ectothermic embryos, like birds, because of temperature effects. Temperatures experienced by ectothermic embryos influence both embryonic development rate and the amount of energy converted into tissue [7,8]. Variation in parental incubation behaviour determines temperatures experienced by avian embryos, and experimental swapping of eggs showed that temperature affects length of the embryonic period [9].…”
Section: Introductionmentioning
confidence: 99%
“…Temporary nest desertion often induces breeding failure in incubating or brooding black-browed albatrosses since the egg or the offspring is quickly predated by lesser sheathbills (Chionis minor) and brown skuas (Catharacta lonnbergi) when left alone. In addition, temporary nest desertion reduces the likelihood of an egg or a chick to hatch or fledge, respectively, because of cooling the egg and important metabolic costs for the chick (Olson et al 2006). In our study, we captured and quickly blood sampled albatross parents when they had already been relieved from brooding duty by their mate.…”
Section: Reproductive Performancementioning
confidence: 99%
“…Embryos of many ectotherm species experience lower growth efficiency and require more energy in colder environments that thereby yield longer embryonic periods and smaller and lower-quality hatchlings (5-10). Bird embryos are ectothermic, especially during early incubation, and embryos develop best at quite high (i.e., 35.5-39.5°C) temperatures associated with the high body temperatures of birds (11)(12)(13)(14)(15). Even maximum ambient temperatures in midelevation tropics (e.g., 25°C) are quite cold relative to bird embryonic development (16).…”
mentioning
confidence: 99%
“…Absences are commonly longer among tropical birds, causing egg temperatures to commonly drop as low as 18°C and average colder temperatures than north temperate relatives (16). Colder egg temperatures cause greater energy requirements by embryos and reduced growth efficiency that yield smaller offspring (11)(12)(13) and longer embryonic periods (16). Moreover, longer embryonic periods also increase the amount of energy needed by the embryo (13,17).…”
mentioning
confidence: 99%